Twofold stationary states in the classical spin-Hall effect. (9th November 2017) - Wegrowe, J-E
Abstract: The stationary states occurring in spin-Hall devices are investigated within the framework of the phenomenological two spin-channel model. It is shown that two different stationary states can be defined, which depends on the redistribution of the electric charges between the two spin-channels during the transient time. A first stationary state can be reached if the charge accumulation occurs inside each spin channel independently, while a second stationary state is reached if the two spin channels are undifferentiated from the point of view of the electric charge accumulation. The screening equations that describe the accumulation of electric charges due to spin–orbit coupling are derived in both cases, and the two stationary states are discussed in terms of the Dyakonov–Perel transport equations. It is shown that the equations should be generalized to spin-dependent electric fields in order to take into account the first stationary state. In both cases, the phenomenology is compatible with experimental observations.